Aromatic polyamide ultrafiltration membrane and preparation method thereof
By preparing an aromatic polyamide ultrafiltration membrane containing a triazole fused ring, the problems of insufficient solvent resistance and mechanical properties of traditional ultrafiltration membranes were solved, achieving high strength, acid and alkali resistance, and fouling resistance, thus extending service life and reducing energy consumption.
Patent Information
- Application Number
- CN202511311673.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2025-10-24
- Estimated Expiration
- 2045-09-15
AI Technical Summary
Traditional ultrafiltration membranes are easily corroded in chemical environments such as strong acids, strong alkalis, and organic solvents. They have insufficient solvent resistance and mechanical properties, are easily contaminated, leading to flux decline, short service life, and high maintenance costs.
Ultrafiltration membranes with high strength and high modulus were prepared by using aromatic polyamide materials and synthesizing polymers containing triazole fused rings through low-temperature polymerization. Combined with pore-forming agents and phase inversion technology, ultrafiltration membranes were prepared.
It improves the chemical stability and antifouling ability of ultrafiltration membranes, extends their service life, reduces overall energy consumption, and enhances the temperature resistance and anti-biofouling performance of membrane materials.
Smart Images

Figure CN120827804A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to an aromatic polyamide ultrafiltration membrane and a preparation method thereof, and belongs to the technical field of ultrafiltration membrane preparation. BACKGROUND
[0002] Ultrafiltration membrane (UF) is a kind of semi-permeable membrane with asymmetric microporous structure, and its filtering principle is based on the screening effect and the interaction between the membrane surface and the solute molecules. The pore size of the ultrafiltration membrane is usually between 0.001-0.1 μm, which can effectively remove macromolecular organic matter, colloid, suspended particles and other impurities in water, and the removal rate of some bacteria and viruses can reach more than 99%, which has been widely used in water treatment, electronics, energy, biotechnology, chemistry and other fields.
[0003] Traditional ultrafiltration membrane materials such as polysulfone (PS) and polyacrylonitrile (PAN) are used to prepare ultrafiltration membranes disclosed in patent applications with publication numbers CN112370978A, CN102755844A and CN117983075A, but these materials have relatively low strength and modulus. In actual application, especially when dealing with fluids with high suspended solids content and high pressure, problems such as membrane filament rupture and membrane module damage often occur, resulting in shortened service life of the ultrafiltration membrane and increased maintenance cost. The resistance to strong acid, strong base and organic solvent is limited. In the wastewater treatment of chemical and pharmaceutical industries, the wastewater often contains various corrosive substances, and the traditional ultrafiltration membrane is easily corroded in such environment, resulting in decreased membrane performance, reduced filtration precision, and even unable to work normally. When dealing with chemical wastewater containing high concentration of acid and alkali, the traditional ultrafiltration membrane may have problems such as membrane hole deformation and membrane material dissolution in a short time. It is easily polluted by organic matter, microorganisms, colloid and other impurities in water, resulting in rapid decline of membrane flux. Once the membrane is polluted, frequent chemical cleaning or physical cleaning is required, which not only increases the operation cost, but also may cause damage to the membrane during the cleaning process, further shortening the service life of the membrane.
[0004] Aromatic polyamide is a kind of high polymer material with high strength, high modulus, high temperature resistance and chemical corrosion resistance. Its molecular structure is mainly composed of amide bond (-CO-NH-) connecting benzene ring. The benzene ring is a highly stable hexagonal ring structure with a strong conjugated system, which can give the material high strength. After the amide bond connects the benzene ring, the molecular chain has good regularity, so that the crystallinity and orientation degree of the polyamide are high, thereby enhancing the mechanical properties and heat resistance of the fiber. However, the conventional aromatic polyamide prepared ultrafiltration membrane also has some limitations, such as certain limitations in use temperature, and in the use process of the ultrafiltration membrane, organic matter and microorganisms are easily adsorbed on the membrane surface, which causes the ultrafiltration membrane to be easily polluted, and the flux of the ultrafiltration membrane is attenuated due to microbial pollution in the long-term use process. SUMMARY
[0005] The present application provides an aromatic polyamide ultrafiltration membrane and a preparation method thereof to solve the problems in the prior art.
[0006] The technical scheme for solving the above technical problem is as follows: a preparation method of an aromatic polyamide ultrafiltration membrane, the preparation method comprising: S1, polymer powder is obtained by low-temperature polymerization reaction of diamine monomers and acyl chloride monomers and post-treatment; the diamine monomers comprise triazole-containing diamine monomers; S2, the polymer powder, a pore-forming agent and sulfuric acid are mixed to obtain a casting solution; S3, the casting solution is spread on a film, and the aromatic polyamide ultrafiltration membrane is obtained through phase inversion and washing.
[0007] Further, the triazole-containing diamine monomers comprise 4,4'-diamino-3,3'-bis(1,2,4-triazole) biphenyl; and the acyl chloride monomers are terephthaloyl chloride. The molar ratio of the diamine monomers to the acyl chloride monomers is 1:(0.95-1.05).
[0008] Further, the diamine monomers comprise triazole-containing diamine monomers and phenylenediamine, and the phenylenediamine is p-phenylenediamine or m-phenylenediamine. The molar proportion of the triazole-containing diamine monomers in the diamine monomers is not less than 50%.
[0009] Further, the specific operation of step S1 is as follows: the diamine monomers are dissolved in an organic solvent containing a cosolvent, the reaction temperature in the system is controlled to be-5-10℃, the acyl chloride monomers are added in batches for low-temperature polycondensation reaction, and after the reaction is completed, the polymer solid is obtained through neutralization and drying, and the polymer powder is obtained through crushing, water washing and drying of the polymer solid.
[0010] Further, the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide. The cosolvent is at least one of calcium chloride and lithium chloride.
[0011] Further, the acyl chloride monomers are added into the reaction system in two batches, the first batch accounts for 30%-60% of the total weight of the acyl chloride monomers, and the second batch accounts for 40%-70% of the total weight of the acyl chloride monomers; the time interval between the addition of the two batches of acyl chloride monomers is 10-15 min; and the reaction time after the addition of the second batch of acyl chloride monomers is 20-40 min.
[0012] Further, in step S2, the pore-forming agent is polyvinylpyrrolidone or polyethylene glycol. In the casting solution, the mass ratio of the pore-forming agent and the polymer powder is 1: (2-5), and the mass content of the polymer powder in the casting solution is 8-12%.
[0013] Further, in step S3, the film laying process is pouring the casting solution on a smooth glass plate, scraping into a flat plate film, and then immersing in a 2%-6% sulfuric acid aqueous solution to realize phase inversion to obtain a solid-state film; the solid-state film is immersed in deionized water for multiple times to obtain the aromatic polyamide ultrafiltration membrane.
[0014] Further, the preparation method of the triazole-containing diamine monomer is as follows: 3,3',4,4'-diphenyltetramine, Cu(OAc)2·H2O, 2,2'-dipyridyl and potassium carbonate are added in a solvent, then 1H-1,2,4-triazole is added for reaction, the reaction temperature is controlled at 20-25℃, after the reaction is completed, the triazole-containing diamine monomer is obtained through post-treatment.
[0015] The application further discloses an aromatic polyamide ultrafiltration membrane, which is prepared by the preparation method.
[0016] The application has the following beneficial effects:
[0017] The application provides a solvent-resistant aromatic polyamide membrane material containing a triazole condensed ring group, the benzene rings in the aromatic polyamide membrane material are arranged regularly, and the aromatic polyamide membrane material contains a large conjugated benzene ring unit, so that the aromatic polyamide membrane material has a linear rigid structure. Moreover, the hydrogen atoms on the amide groups can form hydrogen bonds with the electron-donating carbonyl groups on another molecular chain, so that the hydrogen bonds are crosslinked between the molecular chains, strong intermolecular forces are formed, and the aromatic polyamide is endowed with unique high-strength and high-modulus characteristics. The synthesized aromatic polyamide and the prepared membrane material have the filtering performance of traditional ultrafiltration membrane materials and the chemical stability and mechanical performance of the aromatic polyamide itself.
[0018] The application introduces a 4,4'-diamino-3,3'-bis (1,2,4-triazole) biphenyl monomer into the original aromatic polyamide molecular chain. The triazole condensed ring contained in the monomer has super strong conjugate stability, is more resistant to oxidation and reduction than the traditional benzene ring, can further strengthen the rigidity of the molecular chain, and can improve the long-term temperature resistance of the membrane material to 150℃, which breaks through the upper limit of 80-100℃ of the original temperature resistance. Moreover, the N atoms on the triazole ring can form weak hydrogen bonds, reduce the adsorption capacity of organic matters and microorganisms on the membrane surface, significantly improve the anti-biofouling performance, and solve the problem that the flux of the traditional membrane is attenuated due to microbial pollution in long-term use.
[0019] In addition, the present invention uses aromatic polyamide as the ultrafiltration membrane. The high strength of aromatic polyamide can improve the mechanical properties, acid and alkali resistance, and solvent resistance of the membrane material, thereby enhancing the chemical stability of the ultrafiltration membrane. Moreover, after the ultrafiltration membrane's life cycle, the aramid material therein can be recycled and reused through a specific process to produce products such as aramid pulp, reducing waste generation and environmental pollution. Aramid ultrafiltration membranes have a long service life and strong anti-pollution capabilities. Throughout their entire life cycle, their comprehensive energy consumption is lower than that of traditional ultrafiltration membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM cross-sectional view of the aromatic polyamide film prepared in Example 1. DETAILED DESCRIPTION
[0021] To make the above-mentioned objects, features, and advantages of the present invention more readily apparent, specific embodiments of the present invention are described in detail below. The following description sets forth numerous specific details to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art may make similar modifications without departing from the scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0023] A method for preparing an aromatic polyamide ultrafiltration membrane, comprising: S1, diamine monomer and acyl chloride monomer are polymerized at low temperature and then post-treated to obtain polymer powder; the diamine monomer includes a diamine monomer containing triazole; S2, mixing the polymer powder, porogen and sulfuric acid to obtain a casting solution; S3, laying the casting solution into a membrane, and obtaining an aromatic polyamide ultrafiltration membrane through phase conversion and washing.
[0024] Specifically, the triazole-containing diamine monomer includes 4,4'-diamino-3,3'-bis(1,2,4-triazole)biphenyl; the acyl chloride monomer is terephthaloyl chloride; The molar ratio of the diamine monomer to the acyl chloride monomer is 1:(0.95-1.05).
[0025] Specifically, the diamine monomer includes a diamine monomer containing triazole and phenylenediamine, and the phenylenediamine is p-phenylenediamine or m-phenylenediamine; The mole proportion of the triazole-containing diamine monomer in the diamine monomer is not less than 50%.
[0026] More specifically, the polymer raw material of the aromatic polyamide ultrafiltration membrane comprises the following structural fragment: ; In the above formula, x+y=1, 0 R is or .
[0027] Specifically, the specific operation of step S1 is: dissolving the diamine monomer in an organic solvent containing a cosolvent, controlling the reaction temperature in the system to be-5-10℃, adding the acid chloride monomer in batches for low-temperature polycondensation reaction, after the reaction is completed, neutralizing and drying to obtain polymer solids, and then crushing, washing with water and drying to obtain polymer powder.
[0028] Specifically, the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide. The cosolvent is at least one of calcium chloride and lithium chloride.
[0029] Specifically, the acid chloride monomer is added to the reaction system in two batches, the first batch accounts for 30%-60% of the total weight of the acid chloride monomer, and the second batch accounts for 40%-70% of the total weight of the acid chloride monomer; the interval between the addition of the two batches of acid chloride monomers is 10-15 min; and the reaction time after the addition of the second batch of acid chloride monomers is 20-40 min.
[0030] More specifically, the addition amount of the cosolvent is 7%-10% of the mass of the organic solvent; and the addition mass of the organic solvent is 15-20 times the mass of the diamine monomer. During the low-temperature polycondensation reaction, the stirring speed is 200-300 rpm.
[0031] More specifically, after the polymer solids are crushed by a crusher, they are washed with deionized water for 8-10 times, and then the obtained product is dried in a vacuum oven at-0.8~-1.0 MPa and 80-100℃ for 8-10 h to obtain aromatic polyamide polymer powder. The grinding and crushing process is not specifically limited in the present application, and can be performed according to the processes well known in the art.
[0032] Specifically, in step S2, the pore-forming agent is polyvinylpyrrolidone (PVP K30, molecular weight 40000, National Pharmaceutical Group) or polyethylene glycol (PEG-400, National Pharmaceutical Group). In the casting solution, the mass ratio of the pore-forming agent to the polymer powder is 1:(2-5), and the mass content of the polymer powder in the casting solution is 8-12%.
[0033] More specifically, the preparation process of the casting solution is as follows: the pore-forming agent is added to sulfuric acid under stirring until dissolved, then the polymer powder is added and stirred until the solution is clear and transparent, and then vacuum degassing is performed to obtain the casting solution. The stirring temperature is room temperature, and the stirring time is 8-10 h. The vacuum degassing process is not specifically limited in the present application and can be performed according to the process well known in the art. The sulfuric acid is commercially available concentrated sulfuric acid with a concentration of 98%.
[0034] Specifically, the film laying process in step S3 is as follows: the casting solution is poured onto a smooth glass plate, scraped into a flat film, and then immersed in a 2%-6% sulfuric acid aqueous solution to achieve phase inversion to obtain a solid-state film; the solid-state film is washed by multiple immersions in deionized water to obtain an aromatic polyamide ultrafiltration membrane.
[0035] More specifically, the film laying process in step S3 is as follows: the casting solution is poured onto a smooth glass plate, immediately scraped into a flat film using a scraper with a gap of 100 μm at 25°C, and then immersed in a 2%-6% sulfuric acid aqueous solution until the obtained film falls off from the glass plate to form a solid-state film; the solid-state film is immersed in deionized water for 8 h, and the water is replaced every 1 h to obtain an aromatic polyamide membrane.
[0036] Specifically, the preparation method of the triazole-containing diamine monomer is as follows: 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-dipyridyl, potassium carbonate, and N,N-dimethylformamide are mixed until the solids are dissolved, then 1H-1,2,4-triazole is added, the reaction is carried out for 4-8 h, and then the mixture is poured into ice water to precipitate a light yellow solid. The triazole-containing diamine monomer is obtained by filtration and recrystallization. The reaction temperature is 20-25°C.
[0037] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate, and solvent N,N-dimethylformamide is 1:(2.0-2.5):(2.2-2.6):(10-15), and more preferably 1:2.2:2.5:13.
[0038] The molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, and 2,2'-dipyridyl is 1:0.1:0.2.
[0039] The solvent used in the recrystallization process is preferably a mixed solution of ethanol and water, and the mass ratio of ethanol to water is 1:1.
[0040] In the present application, the required raw materials for preparation are all commercially available products well known to those skilled in the art, unless otherwise specified.
[0041] The application further discloses the aromatic polyamide ultrafiltration membrane prepared by the preparation method.
[0042] Example 1 A preparation method of an aromatic polyamide ultrafiltration membrane is as follows: (1) 3,3',4,4'-diphenyltetramine, Cu(OAc)2·H2O, 2,2'-dipyridyl, potassium carbonate and N,N-dimethylformamide are added into a reaction bottle with a magnetic stirrer to dissolve the solids, and then 1H-1,2,4-triazole is added, the mixture is reacted at 25°C for 5 hours, and then is poured into ice water to precipitate a light yellow solid. The light yellow solid is filtered and recrystallized (ethanol:water = 1:1) to obtain a triazole-containing diamine monomer.
[0043] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate and N,N-dimethylformamide is 1:2.2:2.5:13; and the molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2·H2O and 2,2'-dipyridyl is 1:0.1:0.2.
[0044] (2) Lithium chloride and N-methyl pyrrolidone (NMP) are added into a reaction bottle with a nitrogen inlet, a thermometer and a mechanical stirrer to dissolve completely, and then the triazole-containing diamine monomer prepared in step (1) is added and stirred to dissolve, and the temperature of the system is controlled to be 5°C. Para-terephthaloyl chloride is added in two batches: 50% of the total amount is added at first, and the mixture is stirred rapidly (200 rpm) for 10 minutes; and the remaining 50% is added at second, and the mixture is continuously stirred for 30 minutes, and the temperature is kept at 5°C. After the reaction is completed, flocculent polymer granules are obtained.
[0045] The amount of the added cosolvent is 7.5% of the mass of the organic solvent, the amount of the organic solvent is 20 times of the mass of the diamine monomer, and the molar ratio of the diamine monomer and the acyl chloride monomer is 1:1.
[0046] (3) The polymer granules are poured into a pulverizer for crushing, and are washed with deionized water for 8 times until the washing liquid is neutral. The washed product is dried in a vacuum oven (-0.9 MPa, 90°C) for 10 hours to obtain aromatic polyamide polymer powder.
[0047] (4) Polyvinylpyrrolidone (PVP) is added into concentrated sulfuric acid, and is stirred at room temperature until dissolved, and then the polymer powder is added, and the mixture is stirred for 10 hours until the solution is clear and transparent. After vacuum degassing, the casting solution is poured onto a glass plate, and a 100 μm doctor blade is used to scrape the solution into a film at 25°C, and the film is immediately immersed into a 5% sulfuric acid aqueous solution for solidification, and the film is taken off from the glass plate. The polymer film is soaked in deionized water for 8 hours (the water is changed every 1 hour), and an aromatic polyamide ultrafiltration membrane is prepared.
[0048] The mass ratio of the porogen and the polymer powder is 1:2, and the mass content of the polymer powder in the casting solution is 8%.
[0049] Example 2 A preparation method of an aromatic polyamide ultrafiltration membrane is as follows: (1) A reaction bottle with a magnetic stirrer is added with 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-bipyridine, potassium carbonate and N,N-dimethylformamide to dissolve the solids, and then 1H-1,2,4-triazole is added. After reaction at 25°C for 5 hours, the reaction mixture is poured into ice water to precipitate a light yellow solid. The light yellow solid is filtered and recrystallized (ethanol:water = 1:1) to obtain a triazole-containing diamine monomer.
[0050] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate and solvent N,N-dimethylformamide is 1:2.2:2.5:13, and the molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O and 2,2'-bipyridine is 1:0.1:0.2.
[0051] (2) A reaction bottle with a nitrogen inlet, a thermometer and a mechanical stirrer is added with calcium chloride and N,N-dimethylacetamide (NMAc) and stirred until completely dissolved. Then the triazole-containing diamine monomer prepared in step (1) is added and stirred until dissolved, and the temperature of the system is controlled at 5°C. Terephthaloyl chloride is added in two batches: the first batch is 60% of the total amount, and is quickly stirred (200 rpm) for 10 minutes; the second batch is the remaining 40%, and the stirring is continued for 30 minutes to keep the temperature at 5°C. After the reaction is completed, flocculent polymer particles are obtained.
[0052] The amount of the added cosolvent is 10% of the mass of the organic solvent, the amount of the organic solvent is 15 times the mass of the diamine monomer, and the molar ratio of the diamine monomer and the acyl chloride monomer is 1:1.05.
[0053] (3) The polymer particles are poured into a crusher and crushed, and then washed with deionized water for 8 times until the washing liquid is neutral. The washed product is dried in a vacuum oven (-0.9 MPa, 90°C) for 10 hours to obtain an aromatic polyamide polymer powder.
[0054] (4) Polyethylene glycol (PEG-400) is added to concentrated sulfuric acid, stirred at room temperature until dissolved, then the polymer powder is added, and stirred for 10 hours until the solution is clear and transparent. After vacuum degassing, the casting solution is poured onto a glass plate, and a 100 μm doctor blade is used to scrape the film at 25°C, immediately immersed in a 2% sulfuric acid aqueous solution for solidification, and then the film is removed from the glass plate. The polymer membrane is soaked in deionized water for 8 hours (the water is changed every 1 hour), and an aromatic polyamide ultrafiltration membrane is prepared.
[0055] The mass ratio of the porogen and the polymer powder is 1:4, and the mass content of the polymer powder in the casting solution is 8%.
[0056] Example 3 A preparation method of an aromatic polyamide ultrafiltration membrane is as follows: (1) A reaction bottle with a magnetic stirrer is added with 3,3',4,4'-diphenyltetramine, Cu(OAc)2·H2O, 2,2'-bipyridine, potassium carbonate and N,N-dimethylformamide, mixed until the solids are dissolved, and then 1H-1,2,4-triazole is added. After reaction at 20°C for 6 hours, the reaction mixture is poured into ice water to precipitate a light yellow solid. The product is obtained by filtration and recrystallization (ethanol:water = 1:1) to obtain a triazole-containing diamine monomer.
[0057] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate, and solvent N,N-dimethylformamide is 1:2.2:2.5:13; the molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2·H2O, and 2,2'-bipyridine is 1:0.1:0.2.
[0058] (2) A reaction bottle with a nitrogen inlet, a thermometer and a mechanical stirrer is added with lithium chloride and N-methyl pyrrolidone (NMP) and stirred until completely dissolved. Then, the triazole-containing diamine monomer prepared in step (1) and p-phenylenediamine are added and stirred until dissolved, and the temperature of the system is controlled at 5°C. The p-phthaloyl chloride is added in two batches: the first batch is 40% of the total amount, and the stirring speed is 200 rpm; the second batch is the remaining 60%, and the stirring is continued for 30 min while the temperature is maintained at 5°C. After the reaction is completed, a flocculent polymer granular material is obtained.
[0059] The amount of the added cosolvent is 8% of the mass of the organic solvent, the amount of the organic solvent is 19 times the mass of the diamine monomer, and the molar ratio of the triazole-containing diamine monomer, p-phenylenediamine and p-phthaloyl chloride is 0.5:0.5:1.
[0060] (3) The polymer granular material is poured into a crusher and crushed, and then washed with deionized water for 8 times until the washing liquid is neutral. The washed product is dried in a vacuum oven (-0.9 MPa, 90°C) for 10 hours to obtain an aromatic polyamide polymer powder.
[0061] (4) Polyvinylpyrrolidone (PVP) was added into concentrated sulfuric acid, stirred at room temperature until dissolved, then polymer powder was added, stirred for 10 hours until the solution was clear and transparent, after vacuum degassing, the casting solution was poured onto a glass plate, a 100 μm doctor blade was used to scrape the film at 25°C, immediately immersed in 6% sulfuric acid aqueous solution for solidification, and the film was allowed to fall off from the glass plate. The aromatic polyamide ultrafiltration membrane was prepared by immersing the polymer film in deionized water for 8 hours (water was changed every 1 hour).
[0062] The mass ratio of the porogen and the polymer powder was 1:2, and the mass content of the polymer powder in the casting solution was 8%.
[0063] Example 4 A preparation method of an aromatic polyamide ultrafiltration membrane was as follows: (1) A reaction bottle with a magnetic stirrer was added with 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-bipyridine, potassium carbonate and N,N-dimethylformamide, mixed until the solids were dissolved, then 1H-1,2,4-triazole was added, and after reaction at 25°C for 5 h, the mixture was poured into ice water to precipitate a light yellow solid. The light yellow solid was filtered and recrystallized (ethanol:water = 1:1) to obtain a triazole-containing diamine monomer.
[0064] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate, and solvent N,N-dimethylformamide was 1:2.2:2.5:13; the molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, and 2,2'-bipyridine was 1:0.1:0.2.
[0065] (2) A reaction bottle with a nitrogen inlet, a thermometer and a mechanical stirrer was added with lithium chloride and dimethyl sulfoxide (DMSO) and stirred until completely dissolved. Then m-phenylenediamine and the triazole-containing diamine monomer prepared in step (1) were added and stirred until dissolved, and the temperature of the system was controlled at 5°C. Terephthaloyl chloride was added in two batches: the first batch was 40% of the total amount, and was quickly stirred (200 rpm) for 10 min; the second batch was the remaining 60%, and the stirring was continued for 30 min to keep the temperature at 5°C. After the reaction was completed, flocculent polymer particles were obtained.
[0066] The amount of the added cosolvent was 10% of the mass of the organic solvent, the amount of the organic solvent was 20 times the mass of the diamine monomer, and the molar ratio of the triazole-containing diamine monomer, m-phenylenediamine and terephthaloyl chloride was 0.7:0.3:1.
[0067] (3) The polymer pellets were poured into a crusher for crushing, and washed with deionized water for 8 times until the washing liquid was neutral. The washed product was dried in a vacuum oven (-0.9 MPa, 90°C) for 10 hours to obtain aromatic polyamide polymer powder.
[0068] (4) Polyvinylpyrrolidone (PVP) was added into concentrated sulfuric acid, stirred at room temperature until dissolved, then the polymer powder was added, stirred for 10 hours until the solution was clear and transparent, and after vacuum degassing, the casting solution was poured onto a glass plate, and a 100 μm doctor blade was used to scrape a film at 25°C, immediately immersed in 3% sulfuric acid aqueous solution for solidification, and the film was removed from the glass plate. The polymer membrane was soaked in deionized water for 8 hours (water was changed every 1 hour), and an aromatic polyamide ultrafiltration membrane was prepared.
[0069] The mass ratio of the porogen and the polymer powder was 1:2, and the mass content of the polymer powder in the casting solution was 8%.
[0070] Example 5 A preparation method of an aromatic polyamide ultrafiltration membrane is as follows: (1) A reaction bottle with a magnetic stirrer was added with 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-bipyridine, potassium carbonate and N,N-dimethylformamide, mixed until the solids were dissolved, then 1H-1,2,4-triazole was added, and after reaction at 25°C for 5h, it was poured into ice water to precipitate a light yellow solid. After filtration and recrystallization (ethanol:water=1:1), a triazole-containing diamine monomer was obtained.
[0071] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate, and solvent N,N-dimethylformamide was 1:2.2:2.5:13; the molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-bipyridine was 1:0.1:0.2.
[0072] (2) A reaction bottle with a nitrogen inlet, a thermometer and a mechanical stirrer was added with lithium chloride and N-methylpyrrolidone (NMP) and stirred until completely dissolved. Then m-phenylenediamine and the triazole-containing diamine monomer prepared in step (1) were added and stirred until dissolved, and the system temperature was controlled at 5°C. The terephthaloyl chloride was added in two batches: the first batch was 50% of the total amount, and was quickly stirred (200 rpm) for 10 min; the second batch was the remaining 50%, and the stirring reaction was continued for 30 min, keeping the temperature at 5°C. After the reaction was completed, flocculent polymer pellets were obtained.
[0073] The amount of the cosolvent added is 7% of the mass of the organic solvent, the amount of the organic solvent is 20 times the mass of the diamine monomer, and the molar ratio of the triazole-containing diamine monomer, m-phenylenediamine, and terephthaloyl chloride is 0.8:0.2:1.
[0074] (3) The polymer pellets were poured into a crusher for crushing, and washed with deionized water for 8 times until the washing liquid was neutral. The washed product was dried in a vacuum oven (-0.9 MPa, 90°C) for 10 hours to obtain aromatic polyamide polymer powder.
[0075] (4) Polyvinylpyrrolidone (PVP) was added to 200 g of concentrated sulfuric acid, stirred at room temperature until dissolved, then the polymer powder was added, stirred for 10 hours until the solution was clear and transparent, and after vacuum degassing, the casting solution was poured onto a glass plate, and a 100 μm doctor blade was used to scrape a film at 25°C, immediately immersed in a 5% sulfuric acid aqueous solution for solidification, and the film was allowed to fall off from the glass plate. The polymer membrane was soaked in deionized water for 8 hours (water was changed every 1 hour), and an aromatic polyamide ultrafiltration membrane was prepared.
[0076] The mass ratio of the porogen and the polymer powder is 1:5, and the mass content of the polymer powder in the casting solution is 10%.
[0077] Comparative Example 1 An ultrafiltration membrane was prepared by the same method as in Example 1, except that the diamine monomer used in this comparative example did not include a triazole-containing diamine monomer, and the diamine monomer used was p-phenylenediamine. The specific preparation process is as follows: (1) Lithium chloride and N-methylpyrrolidone (NMP) were added to a reaction bottle with a nitrogen inlet, a thermometer, and a mechanical stirrer, and stirred until completely dissolved. Then p-phenylenediamine was added and stirred until dissolved, and the system temperature was controlled at 5°C. Terephthaloyl chloride was added in two batches: the first batch was 50% of the total amount, and was quickly stirred (200 rpm) for 10 min; the second batch was the remaining 50%, and the stirring was continued for 30 min, keeping the temperature at 5°C. After the reaction was completed, flocculent polymer pellets were obtained.
[0078] The amount of the cosolvent added is 7.5% of the mass of the organic solvent, the amount of the organic solvent is 20 times the mass of the diamine monomer, and the molar ratio of the diamine monomer and the acyl chloride monomer is 1:1.
[0079] (2) The polymer pellets were poured into a crusher for crushing, and washed with deionized water for 8 times until the washing liquid was neutral. The washed product was dried in a vacuum oven (-0.9 MPa, 90°C) for 10 hours to obtain aromatic polyamide polymer powder.
[0080] (3) Polyvinylpyrrolidone (PVP) was added to concentrated sulfuric acid, stirred at room temperature until dissolved, then polymer powder was added, stirred for 10 hours until the solution was clear and transparent, after vacuum degassing, the casting solution was poured onto a glass plate, a 100 μm doctor blade was used to scrape the film at 25°C, immediately immersed in 5% sulfuric acid aqueous solution for solidification, and the film was removed from the glass plate. The polymer membrane was soaked in deionized water for 8 hours (water was changed every 1 hour), and an aromatic polyamide ultrafiltration membrane was prepared.
[0081] The mass ratio of the porogen and the polymer powder was 1:2, and the mass content of the polymer powder in the casting solution was 8%.
[0082] Comparative Example 2 An ultrafiltration membrane was prepared by the same method as in Example 1, except that the diamine monomer used in this comparative example did not include a triazole-containing diamine monomer, and the diamine monomer used was m-phenylenediamine. The specific preparation process was as follows: (1) Lithium chloride and N-methylpyrrolidone (NMP) were added to a reaction bottle with a nitrogen inlet, a thermometer and a mechanical stirrer, and stirred until completely dissolved. Then m-phenylenediamine was added and stirred until dissolved, and the system temperature was controlled at 5°C. The terephthaloyl chloride was added in two batches: the first batch was 50% of the total amount, and was quickly stirred (200 rpm) for 10 min; the second batch was the remaining 50%, and the stirring was continued for 30 min, keeping the temperature at 5°C. After the reaction was completed, flocculent polymer granules were obtained.
[0083] The amount of cosolvent added was 7.5% of the mass of the organic solvent, the amount of organic solvent used was 20 times the mass of the diamine monomer, and the molar ratio of the diamine monomer to the acyl chloride monomer was 1:1.
[0084] (2) The polymer granules were poured into a crusher and washed with deionized water for 8 times until the washing liquid was neutral. The washed product was dried in a vacuum oven (-0.9 MPa, 90°C) for 10 hours to obtain aromatic polyamide polymer powder.
[0085] (3) Polyvinylpyrrolidone (PVP) was added to concentrated sulfuric acid, stirred at room temperature until dissolved, then polymer powder was added, stirred for 10 hours until the solution was clear and transparent, after vacuum degassing, the casting solution was poured onto a glass plate, a 100 μm doctor blade was used to scrape the film at 25°C, immediately immersed in 5% sulfuric acid aqueous solution for solidification, and the film was removed from the glass plate. The polymer membrane was soaked in deionized water for 8 hours (water was changed every 1 hour), and an aromatic polyamide ultrafiltration membrane was prepared.
[0086] The mass ratio of the porogen and the polymer powder was 1:2, and the mass content of the polymer powder in the casting solution was 8%.
[0087] Comparative Example 3 The same method as in Example 5 was used to prepare the ultrafiltration membrane, except that in this comparative example 3, after the film was scraped, it was cured in deionized water to form a film, and the preparation process was as follows: (1) A reaction bottle with a magnetic stirrer was added with 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-bipyridine, potassium carbonate and N,N-dimethylformamide to dissolve the solids, and then 1H-1,2,4-triazole was added. After 5h of reaction at 25℃, it was poured into ice water to precipitate a light yellow solid. After filtration and recrystallization (ethanol:water = 1:1), a triazole-containing diamine monomer was obtained.
[0088] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate, and solvent N,N-dimethylformamide was 1:2.2:2.5:13; the molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, and 2,2'-bipyridine was 1:0.1:0.2.
[0089] (2) A reaction bottle with a nitrogen inlet, thermometer and mechanical stirrer was added with lithium chloride and N-methyl pyrrolidone (NMP) and stirred until completely dissolved. Then m-phenylenediamine and the triazole-containing diamine monomer prepared in step (1) were added and stirred until dissolved, and the system temperature was controlled at 5℃. Terephthaloyl chloride was added in two batches: the first batch was 50% of the total amount, and was quickly stirred (200 rpm) for 10 min; the second batch was the remaining 50%, and the stirring was continued for 30 min to keep the temperature at 5℃. After the reaction was completed, flocculent polymer granules were obtained.
[0090] The amount of cosolvent added was 7% of the mass of the organic solvent, the amount of organic solvent was 20 times the mass of the diamine monomer, and the molar ratio of the triazole-containing diamine monomer, m-phenylenediamine and terephthaloyl chloride was 0.8:0.2:1.
[0091] (3) The polymer granules were poured into a crusher and washed with deionized water for 8 times until the washing liquid was neutral. The washed product was dried in a vacuum oven (-0.9 MPa, 90℃) for 10 hours to obtain aromatic polyamide polymer powder.
[0092] (4) Polyvinylpyrrolidone (PVP) was added to 200g concentrated sulfuric acid, stirred at room temperature until dissolved, then the polymer powder was added, stirred for 10 hours until the solution was clear and transparent, vacuum degassing, then the casting solution was poured onto a glass plate, a 100μm doctor blade was used to scrape the film at 25℃, immediately immersed in deionized water for curing, and the film was removed from the glass plate. The polymer membrane was soaked in deionized water for 8 hours (every 1 hour the water was changed), and an aromatic polyamide ultrafiltration membrane was prepared.
[0093] The mass ratio of the porogen and the polymer powder is 1:5, and the mass content of the polymer powder in the casting solution is 10%.
[0094] Comparative Example 4 The ultrafiltration membrane was prepared by the same method as in Example 5, except that in Comparative Example 4, after the film was scraped, it was cured in a 10% aqueous sulfuric acid solution (higher than the concentration defined in the application) to form a film, and the specific preparation process was as follows: (1) A reaction bottle with a magnetic stirrer was added with 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-bipyridine, potassium carbonate and N,N-dimethylformamide, mixed to dissolve the solids, then added with 1H-1,2,4-triazole, and after 5h of reaction at 25℃, poured into ice water to precipitate a light yellow solid. After filtration and recrystallization (ethanol:water = 1:1), a triazole-containing diamine monomer was obtained.
[0095] The molar ratio of 3,3',4,4'-diphenyltetramine, 1H-1,2,4-triazole, potassium carbonate, and solvent N,N-dimethylformamide was 1:2.2:2.5:13; the molar ratio of 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, and 2,2'-bipyridine was 1:0.1:0.2.
[0096] (2) A reaction bottle with a nitrogen inlet, thermometer and mechanical stirrer was added with lithium chloride and N-methyl pyrrolidone (NMP) and stirred until completely dissolved. Then the m-phenylenediamine and the triazole-containing diamine monomer prepared in step (1) were added and stirred until dissolved, and the system temperature was controlled at 5℃. The terephthaloyl chloride was added in two batches: the first batch was 50% of the total amount, and was quickly stirred (200 rpm) for 10 min; the second batch was the remaining 50%, and the stirring reaction was continued for 30 min, with the temperature maintained at 5℃. After the reaction was completed, flocculent polymer granules were obtained.
[0097] The amount of the added cosolvent was 7% of the mass of the organic solvent, the amount of the organic solvent was 20 times the mass of the diamine monomer, and the molar ratio of the triazole-containing diamine monomer, m-phenylenediamine and terephthaloyl chloride was 0.8:0.2:1.
[0098] (3) The polymer granules were poured into a crusher and crushed, and washed with deionized water for 8 times until the washing liquid was neutral. The washed product was dried in a vacuum oven (-0.9 MPa, 90℃) for 10 hours to obtain aromatic polyamide polymer powder.
[0099] (4) Polyvinylpyrrolidone (PVP) was added into 200 g of concentrated sulfuric acid, stirred at room temperature until dissolved, then polymer powder was added, stirred for 10 hours until the solution was clear and transparent, after vacuum degassing, the casting solution was poured onto a glass plate, a 100 μm doctor blade was used to scrape the film at 25°C, immediately immersed in 10% sulfuric acid aqueous solution for solidification, and the film was allowed to fall off from the glass plate. The aromatic polyamide ultrafiltration membrane was prepared by immersing the polymer membrane in deionized water for 8 hours (changing water every 1 hour).
[0100] The mass ratio of the pore former to the polymer powder was 1:5, and the mass content of the polymer powder in the casting solution was 10%.
[0101] Characterization and performance test 1) The aromatic polyamide ultrafiltration membrane prepared in Example 1 was characterized for morphology, and the cross-sectional morphology was observed using a scanning electron microscope, and the results are shown in FIG. 1. Figure 1 It can be seen from FIG. 1 that the cross-section presents a classic ultrafiltration membrane structure, which is composed of a dense upper skin layer and a support layer composed of finger-like pores. Figure 1
[0102] 2) According to GB / T 1040.3-2006 "Determination of tensile properties of plastics - Part 3: test conditions for films and sheets", the tensile strength and elongation at break of the aromatic polyamide ultrafiltration membranes prepared in the above examples and comparative examples were tested using a universal material testing machine, and the results are shown in Table 1.
[0103] 3) The solvent resistance of the aromatic polyamide ultrafiltration membranes prepared in the examples and comparative examples was tested according to the following method; The ultrafiltration membranes prepared in the examples and comparative examples were cut into 5 cm x 5 cm square samples and dried to constant weight (recorded as initial mass W 0). Acetone, toluene and N,N-dimethylformamide (DMF) were selected as test solvents (covering polar / non-polar solvent types), and the samples were completely immersed in the 25°C solvent for 24 hours. The samples were taken out and the surface solvent was absorbed with filter paper, and weighed (m W 1), and the mass change rate was calculated. The thickness of the membrane before and after immersion was measured using a vernier caliper (t d 0, d 1), and the swelling rate was calculated. According to GB / T1040.3-2006 standard, the tensile strength of the membrane before and after immersion was tested using a universal material testing machine (σ σ 0, σ 1), and the retention rate was calculated. The control sample was a traditional polysulfone (PS) membrane: a commercially available ultrafiltration membrane with the same specifications.
[0104] Formula 1; In formula 1, W 0 and W 1, respectively, are the mass of the membrane before and after soaking.
[0105] Formula 2; In Formula 2, d 0 and d 1, respectively, are the thickness of the membrane before and after soaking.
[0106] Formula 3; In Formula 3, σ 0 and σ 1, respectively, are the tensile strength of the membrane before and after soaking.
[0107] The results obtained are shown in Table 2.
[0108] 4) The aromatic polyamide ultrafiltration membrane prepared in the examples and comparative examples was tested for ultrafiltration performance according to the following method: The pure water flux (J Jw ) and BSA rejection rate (R R ) of the aromatic polyamide ultrafiltration membrane prepared in the examples and comparative examples were tested at 25°C and 0.1 MPa pressure, using pure water and 1 g / L aqueous solution of bovine serum albumin (BSA) (simulating macromolecular pollutants) as the test solution, respectively.
[0109] Formula 4 In Formula 4, V is the permeation volume (L); A is the membrane area (m 2 ); t is the permeation time (h).
[0110] Formula 5 In Formula 5, C p is the concentration of BSA in the permeate (mg / L); C f is the concentration of BSA in the raw material solution (mg / L), which is determined by ultraviolet spectrophotometry.
[0111] The results obtained are shown in Table 3.
[0112] 5) The aromatic polyamide ultrafiltration membrane prepared in the examples and comparative examples was tested for anti-pollution performance according to the methods in Table 4, and the specific test results are shown in Table 4.
[0113] The polysulfone membranes in Tables 1-4 were purchased from DeFiltration Technology Co., Ltd., with a pore size of 50-100 nm.
[0114] Table 1 Tensile strength and elongation at break of ultrafiltration membranes
[0115] Table 2 Solvent resistance of ultrafiltration membrane
[0116] Table 3 Ultrafiltration performance of ultrafiltration membrane
[0117] Table 4 Anti-fouling performance of ultrafiltration membrane
[0118] The data in the table above demonstrate that the aromatic polyamide ultrafiltration membranes prepared using the preparation method described herein in Examples 1-5 all maintained fluxes exceeding 150 L / (m²・h), meeting the practical application requirements of ultrafiltration membranes. The aromatic polyamide membranes (97.8%–99.0%) exhibit significantly higher retention rates than conventional polysulfone membranes (95.0%), demonstrating enhanced separation capabilities for macromolecular contaminants. This is attributed to the aromatic polyamide's rigid benzene ring backbone, which forms a regular microporous structure that effectively screens macromolecular solutes. Furthermore, its hydrogen-bonded cross-linked network effectively reduces membrane pore swelling and deformation, maintaining stable separation performance.
[0119] At the same time, the nitrogen atoms on the triazole ring can form weak hydrogen bonds, reducing the van der Waals adsorption of organic matter and microorganisms on the membrane surface, significantly reducing the amount of microbial adhesion, and resolving the pain points of traditional ultrafiltration membranes, such as rapid flux decay and high cleaning frequency caused by biological contamination during long-term operation. Furthermore, the introduction of the triazole fused ring does not destroy the hydrogen bond cross-linking network between the original molecular chains, and the membrane material still maintains its core advantages of high strength and high solvent resistance. By adjusting the addition ratio of the triazole monomer (10%-30%), the membrane's temperature resistance, anti-fouling properties, and ultrafiltration performance can be flexibly balanced, expanding the membrane's application in harsh scenarios such as high-temperature fermentation wastewater and pharmaceutical hot reflux extraction wastewater.
[0120] Aromatic polyamides have a rigid benzene ring skeleton, with para-substituted benzene rings arranged linearly to form highly conjugated rigid chains that inhibit the penetration of solvent molecules. At the same time, the benzene ring conjugated system is highly stable and not easily subjected to electrophilic substitution or oxidation reactions with organic solvents. The amide bonds between adjacent molecular chains form strong intermolecular forces through hydrogen bonds, and the amide bonds are difficult to hydrolyze in aprotic solvents. Aromatic polyamide ultrafiltration membranes achieve a 2-3 times improvement in tensile strength compared to traditional polysulfone membranes. Although some elongation at break is sacrificed, the material's resistance to breakage and long-term stability are significantly enhanced. Based on a comprehensive analysis of ultrafiltration performance and solvent resistance, the aromatic polyamide membranes described in the present invention are particularly suitable for treating wastewater in harsh environments such as chemical and pharmaceutical industries with high loads and strong corrosion.
[0121] From the comparison of the test results of Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that if the diamine monomer does not include a triazole-containing diamine monomer, the ultrafiltration performance and anti-pollution performance of the polymer membrane material are both reduced, because the N atom on the triazole ring can form a weak hydrogen bond, the adsorption of pollutants on the membrane surface is reduced, the amount of microbial adhesion is significantly reduced, and the rigid benzene ring skeleton of triazole forms a regular microporous structure, effectively screening macromolecular solutes and effectively reducing membrane pore swelling deformation.
[0122] From the comparison of the test results of Comparative Example 3 and Example 5, it can be seen that if the film is cured in deionized water after being scraped into a film, the phase inversion rate is too fast during phase inversion, and a more dense skin layer is formed on the film surface, the permeation resistance of the separated substance in the separation scene is increased, and the permeation performance of the separation membrane is significantly reduced.
[0123] From the comparison of the test results of Comparative Example 3 and Example 5, it can be seen that if the film is cured in a high-concentration sulfuric acid aqueous solution after being scraped into a film, the permeation performance of the polymer membrane is obviously increased, but the retention performance is significantly reduced to below 90%. Dilute sulfuric acid has a certain compatibility with the main solvent, which can slow down the phase separation process during phase inversion, which is beneficial to the formation of a support layer with high porosity and large pore size, thereby increasing the water flux of the membrane, but too high a concentration of sulfuric acid will result in too many large pore structures, which will damage the retention rate of the separation membrane to pollutants.
[0124] The technical features of the above-described embodiments can be combined in any manner. In order to make the description simple, all possible combinations of the technical features in the above-described embodiments are not described, but as long as the combinations of the technical features do not contradict, they should be considered as within the scope of the present disclosure.
[0125] The above-described embodiments only express several embodiments of the present application, and the description is more specific and detailed, but it should not be understood as limiting the scope of the patent. It should be pointed out that for ordinary skilled persons in the art, without departing from the concept of the present application, a number of modifications and improvements can be made, which are within the scope of the present application. Therefore, the protection scope of the present patent should be subject to the appended claims.
Claims
1. A method for producing an aromatic polyamide ultrafiltration membrane, characterized by, The preparation method is: S1, diamine monomers and acyl chloride monomers are polymerized by low-temperature polymerization and post-treated to obtain polymer powder; the diamine monomers include triazole-containing diamine monomers; S2, the polymer powder, a pore-forming agent and sulfuric acid are mixed to obtain a casting solution; S3, the casting solution is spread on a smooth glass plate, and a flat membrane is scraped, and then the membrane is immersed in a 2%-6% sulfuric acid aqueous solution to realize phase inversion to obtain a solid-state membrane; the solid-state membrane is washed by being immersed in deionized water multiple times to obtain an aromatic polyamide ultrafiltration membrane.
2. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 1, characterized in that: The triazole-containing diamine monomers include 4,4'-diamino-3,3'-bis(1,2,4-triazole) biphenyl; and the acyl chloride monomers are terephthaloyl chloride. The molar ratio of the diamine monomers to the acyl chloride monomers is 1:(0.95-1.05).
3. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 1, characterized in that: The diamine monomers include triazole-containing diamine monomers and phenylenediamine, and the phenylenediamine is p-phenylenediamine or m-phenylenediamine. The molar proportion of the triazole-containing diamine monomers in the diamine monomers is not less than 50%.
4. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 1, wherein: The specific operation of step S1 is as follows: the diamine monomers are dissolved in an organic solvent containing a cosolvent, the reaction temperature in the system is controlled to be-5-10℃, the acyl chloride monomers are added in batches for low-temperature polycondensation reaction, and after the reaction is completed, the polymer solid is obtained by neutralization and drying, and the polymer powder is obtained by crushing, water washing and drying of the polymer solid.
5. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 4, characterized in that: The organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide; The cosolvent is at least one of calcium chloride and lithium chloride.
6. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 4, characterized in that: The acyl chloride monomers are added into the reaction system in two batches, the weight of the first batch accounts for 30%-60% of the total weight of the acyl chloride monomers, and the weight of the second batch accounts for 40%-70% of the total weight of the acyl chloride monomers; the interval between the addition times of the two batches of acyl chloride monomers is 10-15 min; and the reaction time after the addition of the second batch of acyl chloride monomers is 20-40 min.
7. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 1, characterized in that: In step S2, the pore-forming agent is polyvinylpyrrolidone or polyethylene glycol; In the casting solution, the mass ratio of the pore-forming agent to the polymer powder is 1:(2-5), and the mass content of the polymer powder in the casting solution is 8-12%.
8. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 1, characterized in that: In step S3, the film spreading process is as follows: the casting solution is poured on a smooth glass plate, a flat membrane is scraped, and then the membrane is immersed in a 2%-6% sulfuric acid aqueous solution to realize phase inversion to obtain a solid-state membrane; and the aromatic polyamide ultrafiltration membrane is obtained by washing the solid-state membrane by being immersed in deionized water multiple times.
9. The method for preparing an aromatic polyamide ultrafiltration membrane according to claim 1, characterized in that: The preparation method of the triazole-containing diamine monomers is as follows: 3,3',4,4'-diphenyltetramine, Cu(OAc)2•H2O, 2,2'-bipyridine and potassium carbonate are added in a solvent, and then 1H-1,2,4-triazole is added for reaction, the reaction temperature is controlled to be 20-25℃, and after the reaction is completed, the triazole-containing diamine monomers are obtained by post-treatment.
10. An aromatic polyamide ultrafiltration membrane, characterized by, The aromatic polyamide ultrafiltration membrane is prepared by the method according to any one of claims 1-9.
Citation Information
Patent Citations
Preparation method for surface ionization modified polysulfone ultrafiltration membrane
CN102755844A
Polysulfone ultrafiltration membrane and preparation method thereof
CN112370978A
Polyacrylonitrile-based conductive ultrafiltration membrane for water treatment and preparation method thereof
CN117983075A
Biphenyl bis-triazole compound as well as preparation method and application thereof
CN104230829A
Preparation method of aromatic polyamide hollow fiber porous membrane
CN104353372A